Coadsorption and subsequent redox conversion behaviors of As(III) and Cr(VI) on Al-containing ferrihydrite. (April 2018) - Ding, Zecong; Fu, Fenglian; Dionysiou, Dionysios D.; Tang, Bing
Abstract: Naturally occurring ferrihydrite often contains various impurities, and Al is one of the most prominent impurities. However, little is known about how these impurities impact the physical and chemical properties of ferrihydrite with respect to metal(loid) adsorption. In this study, a series of Al-containing ferrihydrites were synthesized and exposed to a mixed solution containing As(III) and Cr(VI). The results showed that the two contaminants can be quickly adsorbed onto the surface of Al-containing ferrihydrite under acidic and neutral conditions. With the increase of Al molar percentage in ferrihydrites from 0 to 30, the adsorption capacity of As(III) decreased, whereas it increased for Cr(VI). On the other hand, with the increase of pH value from 3.0 to 11.0, the decreasing rate of As(III) was accelerated first, then slowed down, whereas the Cr(VI) decreasing rate slowed down dramatically. X-ray diffraction (XRD), Brunauer-Emmett-Teller (BET) analysis method, transmission electron microscopy (TEM) analysis, energy dispersive spectroscopy (EDS) mapping, Attenuated Total Reflectance Fourier Transform Infrared Spectroscopy (ATR-FTIR), and X-ray photoelectron spectroscopy (XPS) were employed to characterize Al-containing ferrihydrite. Interestingly, it was found that the redox transformation occurred between As(III) and Cr(VI) after the two contaminants were coadsorbed onto the surface of Al-containing ferrihydrite. The oxidation of As(III) to As(V) and reduction of Cr(VI) to Cr(III) would greatly lower the environmental hazard of the As(III) and Cr(VI). Graphical abstract: Image 1 Highlights: Ferrihydrites with different Al content were successfully synthesized. As(III) and Cr(VI) can be removed rapidly under acidic and neutral condition. Effect of Al content and initial pH on As(III) and Cr(VI) removal were studied. Coadsorption and redox conversion behaviors of As(III) and Cr(VI) were found. Abstract : The redox conversion between As(III) and Cr(VI) occurred after the two contaminants were coadsorbed onto the surface of Al-containing ferrihydrite.